TREM2 is required for microglial instruction of astrocytic synaptic engulfment in neurodevelopment. Issue 10 (2nd July 2019) - Jay, Taylor R.; von Saucken, Victoria E.; Muñoz, Braulio; Codocedo, Juan F.; Atwood, Brady K.; Lamb, Bruce T.; Landreth, Gary E.
Abstract: Variants in the microglial receptor TREM2 confer risk for multiple neurodegenerative diseases. However, it remains unknown how this receptor functions on microglia to modulate these diverse neuropathologies. To understand the role of TREM2 on microglia more generally, we investigated changes in microglial function in Trem2 −/− mice. We found that loss of TREM2 impairs normal neurodevelopment, resulting in reduced synapse number across the cortex and hippocampus in 1‐month‐old mice. This reduction in synapse number was not due directly to alterations in interactions between microglia and synapses. Rather, TREM2 was required for microglia to limit synaptic engulfment by astrocytes during development. While these changes were largely normalized later in adulthood, high fat diet administration was sufficient to reinitiate TREM2‐dependent modulation of synapse loss. Together, this identifies a novel role for microglia in instructing synaptic pruning by astrocytes to broadly regulate appropriate synaptic refinement, and suggests novel candidate mechanisms for how TREM2 and microglia could influence synaptic loss in brain injury and disease. Main points: TREM2 is required for establishing appropriate microglial size, territory, and tiling Microglia broadly shape appropriate synapse elimination during neurodevelopment Microglia limit synaptic uptake by astrocytes in development through a TREM2‐dependent mechanism